2002
DOI: 10.1038/415165a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic coding of behaviourally relevant stimuli in parietal cortex

Abstract: A general function of cerebral cortex is to allow the flexible association of sensory stimuli with specific behaviours. Many neurons in parietal, prefrontal and motor cortical areas are activated both by particular movements and by sensory cues that trigger these movements, suggesting a role in linking sensation to action. For example, neurons in the lateral intraparietal area (LIP) encode both the location of visual stimuli and the direction of saccadic eye movements. LIP is not believed to encode non-spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
181
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(202 citation statements)
references
References 20 publications
19
181
2
Order By: Relevance
“…However, recent data provide evidence contrary to this hypothesis (Ferrera et al, 1992(Ferrera et al, , 1994Sereno and Maunsell, 1998;Toth and Assad, 2002). For instance, neurons in the lateral intraparietal (LIP) area, a cortical area in the dorsal (spatial) pathway, are sensitive to the shape of a visual stimulus (which is regarded as a nonspatial attribute); this sensitivity is comparable with that seen in the ventral pathway (Sereno and Maunsell, 1998).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, recent data provide evidence contrary to this hypothesis (Ferrera et al, 1992(Ferrera et al, , 1994Sereno and Maunsell, 1998;Toth and Assad, 2002). For instance, neurons in the lateral intraparietal (LIP) area, a cortical area in the dorsal (spatial) pathway, are sensitive to the shape of a visual stimulus (which is regarded as a nonspatial attribute); this sensitivity is comparable with that seen in the ventral pathway (Sereno and Maunsell, 1998).…”
Section: Introductionmentioning
confidence: 65%
“…For instance, neurons in the lateral intraparietal (LIP) area, a cortical area in the dorsal (spatial) pathway, are sensitive to the shape of a visual stimulus (which is regarded as a nonspatial attribute); this sensitivity is comparable with that seen in the ventral pathway (Sereno and Maunsell, 1998). Other experiments indicate that parietal neurons are modulated by the color of a visual stimulus when it is relevant for the successful completion of a behavioral task (Toth and Assad, 2002). Similarly, we have recently shown that auditory neurons in the lateral intraparietal area are modulated by the nonspatial properties (e.g., spectrotemporal structure) of an auditory stimulus (Gifford and Cohen, 2004b).…”
Section: Introductionmentioning
confidence: 74%
“…However, Lavie (1988, 1993) proposed that visual selection by nonspatial properties such as color may be implemented by selecting the location of the relevant color. PPC might thus fulfill a role in selecting relevant locations even when color defines the targets (Toth and Assad, 2002). Our results showed that rTMS over right (but not left) PPC affected the efficiency of top-down selection by color in a spatially specific manner, with relative suppression of top-down control for the left hemifield but relative enhancement for the right hemifield, particularly for bilateral displays.…”
Section: Introductionmentioning
confidence: 68%
“…Event-related potentials and magnetic field recordings in humans further show that targets defined by nonspatial feature-based selection can subsequently lead to selection of the location of a likely target (Hopf et al, 2004). Moreover, in a recent study on monkeys, Toth and Assad (2002) recorded single-unit activities from the lateral intraparietal sulcus (area LIP), one possible homolog of the human PPC, while the monkeys selected an eye-movement based on the color or location of a visual cue. A number of LIP neurons were found to show colorselective responses when color became the task-relevant property for defining spatial selection, as here.…”
Section: Spatial Specificity Of the Right Ppc Rtms Effectmentioning
confidence: 99%
“…Elevated responses in the lateral intraparietal area (LIP) are associated with increased saliency or behavioral relevancy of stimuli (Colby et al, 1996;Gottlieb et al, 1998;Toth and Assad, 2002) and with increased contrast sensitivity in the receptive field at the behavioral level (Bisley and Goldberg, 2003). In the frontal eye fields (FEF), subthreshold microstimulation causes spatially localized increases in sensitivity both at the behavioral level and in visual cortical neurons (Moore and Fallah, 2001;Moore and Armstrong, 2003;Moore and Fallah, 2004).…”
Section: The Possible Sources and Mechanisms Of Attentional Modulationmentioning
confidence: 99%